A rare complication in a liver transplant patient: Meckel diverticulum perforation due to biliary stent - Topal, Uğur (Int J Surg Case Rep, 2018)
INTRODUCTION: Meckel’s diverticulum is the most common congenital lesion of the small intestine. The incidence varies between 0.5% and 2% Biliary stents can be used for the treatment of patients with bile duct complications. Intestinal perforation due migrated stents is a very rare and life threatening complication. “Perforation of the Meckel diverticulum due to stent”, and no case was found in the literature. For this reason, our case has been identified as the first case seen in the literature. CASE PRESENTATION: A 20 year old male patient liver transplantation was performed from a live donor. 3 years ago The patient presented at our clinic with abdominal pain, nausea and vomiting that has been present for 2 days. Abdominal computed tomography showed a foreign body in the small intestines Patient was operated in emergency conditions. Meckel Diverticulum 40 cm proximal to the ileocecal valve and a biliary drainage catheter perforating the diverticule was seen Meckel's diverticulum was excised, primary repair was performed, Postoperative recovery was uneventful. DISCUSSION: Complication rates due to a biliary stent range between 8–10% with a mortality below 1% (Konstantinidis et al. [1]). The most feared complication due to a biliary stent is stent migration. The perforation rate due to stent migration is below 1%. It most commonly occurs in the duodenum. Patients with stent related perforations are surgically managed as other GIS perforations. CONCLUSIONS: Perforation due to stent migration should also be considered in differential diagnosis in patients with a biliary stent and Acute Abdomen.